IDDF2020-ABS-0182 A novel immunosuppressive role of cholesterol in nafld-associated hepatocarcinogenesis. (18th November 2020) - Tang, Wenshu; Zhou, Jingying; Yang, Weiqin; Feng, Yu; Lee, Heung Man; Lam, Candice CH; Chan, Anthony WH; Wong, Simon KH; Wong, Vincent WS; Kong, Alice PS; Cheng, Alfred SL
Abstract : Background: Hepatocellular carcinoma (HCC) is the fifth most prevalent cancer and the second leading cause of cancer deaths worldwide. Driven by the epidemics of obesity and diabetes, it is anticipated that non-alcoholic fatty liver disease (NAFLD) will become the most important cause of HCC. Emerging evidence suggests that metabolic and immune dysfunction are key features of NAFLD-associated HCC, my research aim to investigate the metabolic-immune dysregulation underlying NAFLD-HCC development. Here we show that aberrant cholesterol accumulation in the liver predisposes cancer development by reprogramming the immunosurveillance microenvironment. Methods: Comprehensive immune profiling in a high-fat high-carbohydrate diet-induced NAFLD murine model was performed. Results: Our results revealed a specific reduction of cytolytic natural killer T (NKT) cells in the liver, which was negatively correlated with the elevated cholesterol level. Cholesterol-lowering drug Rosuvastatin reduced cholesterol level and restored NKT cell proportion and function, which subsequently suppressed the growth of orthotopically-implanted HCC tumor. Inhibition of cholesterol synthesis by an mTORC1/C2 dual kinase inhibitor Vistusertib (AZD2014), or lentiviral-mediated suppression of the mTOR pathway also showed similar effects. Notably, NKT inactivation by a specific CD1d receptor-targeting antibody abolished the anti-tumorigenic effects of both Rosuvastatin and Vistusertib, thus underscoring the casual role of NKT in cholesterol-mediated hepatocarcinogenesis. We also showed a reduction of NKT cells and its negative correlation with cholesterol elevation in obese patients undergone bariatric surgery. Conclusions: Our study elucidates a new immunosuppressive role of cholesterol in establishing a pro-tumorigenic microenvironment. These findings explain why cholesterol-lowering drugs may reduce cancer incidence and provide new therapeutic strategies of revitalizing the immunosurveillant NKT cells for the intervention of NAFLD-associated HCC. This project is supported by the University Grants Committee through the Collaborative Research Fund (C4045-18W), General Research Fund (14108219, 14105419), the Li Ka Shing Foundation and the Terry Fox Foundation and the AstraZeneca Preclinical Oncology Research Program (2017).